Causal association of metabolic syndrome with chronic kidney disease progression: A Mendelian randomization study - Qitong Guo; Meiling Chen; Yihang Yu; Ping Li; Xu Huang; Lianju Shen; Chunlan Long; Xing Liu; Tao Lin; Dawei He; Guanghui Wei; Deying Zhang (Pediatric Discovery)
Abstract Research from the past has indicated a link between the risk of chronic kidney disease (CKD) and metabolic syndrome (MetS). It is yet unknown. Nevertheless, exactly how the dynamic process of declining renal function and metabolic syndrome are related. The study's purpose is to evaluate the causal relationship between MetS and the deterioration in kidney function using a Mendelian randomization (MR). Univariable and multivariable MR were applied to evaluate the causal relationships between MetS and its components with Rapid3, CKDi25, and CKD. The main source of MetS data was the GTC database, whose constituents came from extensive genome‐wide association research. The CKDGen Consortium provided data on dynamic changes in kidney function. Preliminary analysis was conducted using five different statistical techniques, including Inverse Variance Weighting and Weighted Median. Rucker's Q, MR‐Egger, and Cochran's Q test were used in sensitivity studies. In order to address reverse causality, the Steiger test was used. The IVW results showed Rapid3, CKDi25, and CKD all exhibited positive correlations with MetS. Rapid3, CKDi25, and CKD were found to have a positive causal relationship with SBP and WC, while DBP was also linked to an increased risk of Rapid3 and CKDi25. Even after accounting for other variables, MVMR analysis showed a correlation between WC and the drop in kidney function indices. MetS, together with its constituents WC, SBP, and DBP, are separate risk factors for the deterioration of renal function. However, the causal relationship between FBG, HDL, TG, and the decline in kidney function indicators remains uncertain.